2004
DOI: 10.1097/01.rhu.0000120898.82192.f4
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Gout

Abstract: Spinal involvement is considered to be a rare complication of gout. We report a case of a 48-year-old woman with chronic tophaceous gout, recently desensitized to allopurinol, who presented with an L4 radiculopathy. A magnetic resonance image (MRI) of the lumbosacral spine revealed an extradural process at L4 level. Three months before this episode, for unrelated reasons, the patient had an MRI of her entire spine, which was normal. Laminectomy was performed revealing a large gouty tophus. The fact that a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 29 publications
1
18
0
2
Order By: Relevance
“…The low temperature and avascular tissues can decrease the solubility of urate crystals; hence, gout commonly occurs in locations with these conditions10,12,13). Spinal gout can show various concomitant degenerative features, and it has been suggested that factors such as degenerative disease of the spine, tissue necrosis, or spinal injury trigger the process1,3,10). Here, the patient had spondylolysis at the pars interarticularis of L5 bilaterally.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The low temperature and avascular tissues can decrease the solubility of urate crystals; hence, gout commonly occurs in locations with these conditions10,12,13). Spinal gout can show various concomitant degenerative features, and it has been suggested that factors such as degenerative disease of the spine, tissue necrosis, or spinal injury trigger the process1,3,10). Here, the patient had spondylolysis at the pars interarticularis of L5 bilaterally.…”
Section: Discussionmentioning
confidence: 97%
“…However, in rare cases, gouty tophi involve the axial joints including the spine4,8,11,12,18). The reported spinal gout cases present similar clinical manifestations as other spinal diseases, including back/neck pain, radiculopathy, and myelopathy3,4).…”
Section: Introductionmentioning
confidence: 82%
“…The most frequent involvement reported in the literature is the lumbar spine10,14). However, the cervical and thoracic spine can also be affected1,4,5,15,17). Tophaceous crystal deposition in axial elements of the spine is generally found at the facet articulation, but the ligamentum flavum, pedicle, lamina, epidural soft tissue, vertebral body, and disc space can also be affected11,12,16).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, gout affects the distal joints of the appendicular skeleton. The occurrence of gout in the spine has been reported in only a limited number of cases1,2,5,6,8-12,14,16,18).…”
Section: Introductionmentioning
confidence: 99%
“…Хотя этиопатогенез депонирования кристаллов в осевом скелете не изучен, есть мнение, что исходное на-личие дегенеративных заболеваний позвоночника, ткане-вые некрозы, травмы позвоночника могут быть триггер-ными факторами подобных процессов [11,[27][28][29]. В на-шем случае подобных факторов, ассоциирующихся с уве-личенным риском образования тофусов, не было.…”
unclassified